Preoperative imaging and intraoperative navigation of the parathyroid glands neoplasms in primary hyperparathyroidism - K. Yu. Slashchuk; M. V. Degtyarev; P. O. Rumyantsev; A. K. Eremkina; N. V. Tarbaeva; D. G. Beltsevich; I. V. Kim; G. A. Melnicthhenko; N. G. Mokrysheva (Опухоли головы и шеи, 2022)
Introduction. Primary hyperparathyroidism is one of the most common diseases of the endocrine system, after diabetes mellitus and thyroid pathologies. Early diagnosis and treatment of primary hyperparathyroidism allow avoiding severe damage to the bones, kidneys, other organs, thereby reducing the incidence of disability and improving the patients quality of life. The only radical treatment for primary hyperparathyroidism is the surgical removal of the pathologically altered, hyperfunctioning parathyroid glands.The study objective – to increase the efficiency of preoperative topical diagnosis and intraoperative navigation of parathyroid glands.Materials and methods. 200 patients with laboratory-verified primary hyperparathyroidism, who underwent preoperative topical diagnostics (ultrasound, planar scintigraphy and single-photon emission computed tomography, combined with computed tomography (SPECT / CT), in some cases supplemented with contrast enhanced CT with / or fine needle aspiration biopsy with flushing from a needle on for parathyroid hormone) and received surgical treatment, in period from 2017 to 2020. A single-stage, open-label comparative study was carried out, including clinical, laboratory and instrumental data of patients. The follow-up period after surgery for primary hyperparathyroidism was at least 6 months.Results. From 200 included patients, surgical treatment in the amount of minimally invasive parathyroidectomy was performed in 189 patients. As a result of the analysis of the diagnostic accuracy, for a combination of ultrasound and SPECT/CT with augmented contrast enhanced CT, the overall accuracy in visualizing of parathyroid glands was 99 % (95 % confidence interval (CI): 97–100), diagnostic specificity 77 % (95 % CI: 54–100), sensitivity 100 % (95 % CI: 98–100), the predictive value of positive and negative results was 98 % (95 % CI: 97–100) and 100 % (95 % CI: 98–100) respectively.Conclusion. The results allowed us to develop an algorithm for preoperative topical diagnosis of parathyroid glands in patients with laboratory-verified primary hyperparathyroidism and indications for surgical treatmen. We recommend to perform ultrasound of the thyroid and parathyroid glands in all patients at the first stage, in the absence of evident changes in the thyroid gland, at the second stage – scintigraphy and SPECT / CT with 99mTc-MIBI; in cases with significant concomitant functional or structural pathology of the thyroid gland – contrast enhanced CT; if necessary, supplementing fine needle aspiration biopsy with flushing from a needle on for parathyroid hormone.